Eduardo Gil de Muro. Larga conversación con Delibes (Berceo, 2022)
We will divide this article into two parts. First, as an introduction to Gil de Muro's article, we will offer a brief summary of Father Eduardo's biography and subsequently sketch out the historical context. We omit Delibes's biography as it is well known, drawing a parallel between the two figures instead. Next, we will transcribe Eduardo Gil de Muro's “Long Conversation with Delibes.” The text reproduced here was summarized and published under the title “Conversation with Miguel Delibes” in Reseña de literatura, arte y espectáculos, issue 34, Madrid, 1970, pp. 195–206. Here, we present its original and most extensive version.It masterfully blends a study of Delibes's work—from its beginnings up to the 1968–1969 academic year, when we believe Father Eduardo Gil de Muro Quiñones wrote it—with the interview conducted by Eduardo, a budding journalist, with Mr. Miguel Delibes. The article published in 1970 focuses on the interview itself, omitting the short essays Eduardo used to introduce many of his questions. We believe that publishing it in full reveals the true nature of the journalistic and literary work Gil de Muro produced as a journalism student in Madrid. It is the work of a person who, at just over forty years old and with a remarkable literary and journalistic background, interviews one of the most recognized figures of letters in Spain at the time.
Keywords: Array; Array; Array